1994
DOI: 10.1016/0014-5793(94)01139-7
|View full text |Cite
|
Sign up to set email alerts
|

pH‐independent inhibition of restriction endonuclease cleavage via triple helix formation by oligonucleotides containing 8‐oxo‐2′‐deoxyadenosine

Abstract: The ability of homopyrimidine oligonucleotides containing 8-oxo-2'-deoxyadenosine to form stable, triple helical structures with the sequence containing the recognition site for the class II-S restriction enzyme, Ksp632-I, was studied as a function of pH. The 8-0x0-2'-deoxyadenosinesubstituted oligomers were shown to inhibit enzymatic cleavage and to bind within the physiological pH range in a pa-independent fashion without compromising specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A number of base analogs have been designed to circumvent this problem. These include the pyrimidine analogs pseudoisocytosine (21,22), 6-amino-2′-O-methylcytidine (23) and 4-amino-5-methyl-2,6-pyrimidione (24) and the purine analogs 3-methyl-5-amino-1H-pyrazolo [4,3-d]pyrimidin-7-one (19,25,26), 8-oxo-adenine (27)(28)(29)(30) and 6-methyl-8-oxoadenine (31,32). Each of these analogs contains two hydrogen bond donor groups within its structure which can interact with the O-6 and N-7 of G. The 8-oxoadenine analogs are particularly interesting because they are easy to prepare and the nucleoside base adopts the syn conformation, a conformation which enables the analog to contact G with two hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…A number of base analogs have been designed to circumvent this problem. These include the pyrimidine analogs pseudoisocytosine (21,22), 6-amino-2′-O-methylcytidine (23) and 4-amino-5-methyl-2,6-pyrimidione (24) and the purine analogs 3-methyl-5-amino-1H-pyrazolo [4,3-d]pyrimidin-7-one (19,25,26), 8-oxo-adenine (27)(28)(29)(30) and 6-methyl-8-oxoadenine (31,32). Each of these analogs contains two hydrogen bond donor groups within its structure which can interact with the O-6 and N-7 of G. The 8-oxoadenine analogs are particularly interesting because they are easy to prepare and the nucleoside base adopts the syn conformation, a conformation which enables the analog to contact G with two hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…An 8-oxoadenosine derivative may be able to adopt two tautomers, a keto form and an enol form. Footprinting analysis (KRAWCZYK et al 1992) and UV melting analysis WANG et al 1994) have shown that by the replacement of cytidine in the third stand by 8-oxoadenine derivatives, the stability of triple helix becomes independent of buffer pH, suggesting the validity of the predicted structure of the triple helix containing 8-oxoadenine in the third strand. In addition, the glycosidic bond of 8-oxoadenosine seems to exist in the syn conformation preferentially (GUSCHLBAUER et al 1991), which might be required for 8oxoadenosine to form Hoogsteen hydrogen bonding without disturbing backbone positioning of the third strand.…”
Section: Cytidine Derivativesmentioning
confidence: 97%
“…Adenosine Derivatives 8-0xoadenine derivatives (or more precisely, "7,8-dihydro-8-oxoadenine derivatives") including 8-oxoadenosine JEITER and HOBBS 1993;WANG Q et al 1994;MILLER et al 1996) and N 6 -methyl-8-oxoadenosine (YOUNG et al 1991;KRAWCZYK et al 1992) have also been reported to replace cytidine as N 3 -protonated cytidine analogues. Adenosine Derivatives 8-0xoadenine derivatives (or more precisely, "7,8-dihydro-8-oxoadenine derivatives") including 8-oxoadenosine JEITER and HOBBS 1993;WANG Q et al 1994;MILLER et al 1996) and N 6 -methyl-8-oxoadenosine (YOUNG et al 1991;KRAWCZYK et al 1992) have also been reported to replace cytidine as N 3 -protonated cytidine analogues.…”
Section: Cytidine Derivativesmentioning
confidence: 99%
“…We have tested the ability of homopyrimidine RNA and 2′-O-methyl RNA oligonucleotides containing AOH and/or AmOH to inhibit the sequence-specific cleavage of simian virus 40 (SV40) DNA, at neutral and basic pH values, by the class II-S restriction endonuclease, 22). The Ksp632-I enzyme recognizes a 6 base pair homopurine-homopyrimidine sequence.…”
mentioning
confidence: 99%
“…In this paper, we wish to report the possibility of inhibiting sequence-specific DNA binding proteins by RNA and 2‘- O -methyl RNA oligonucletides containing 8-oxo-2‘-adenosine (AOH) and/or 2‘- O -methyladenosine (AmOH) instead of cytidine. We have tested the ability of homopyrimidine RNA and 2‘- O -methyl RNA oligonucleotides containing AOH and/or AmOH to inhibit the sequence-specific cleavage of simian virus 40 (SV40) DNA, at neutral and basic pH values, by the class II-S restriction endonuclease, Ksp 632-I ( , ) . The Ksp 632-I enzyme recognizes a 6 base pair homopurine−homopyrimidine sequence.…”
mentioning
confidence: 99%